Networked automatic test system based on message-oriented middleware - Xiong Fengguang; Han Xie (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Abstract: Aim at thecurrent status of automatic test system that focuses only on a single or thesame type of weapons' performance testing, a networked automatic test system basedon message-oriented middleware is proposed in this paper, and innerarchitecture and process of pus/sub in message-oriented middleware aredescribed. Basing on the message-oriented middleware, the networked automatictest system can shield the complexity and diversity of the bottom test systemand test equipment, and can realize cross-platform communication of varioustest data about weapons. Experiments show that the networked automatic test systembased on message-oriented middleware is an integrated test platform which can providecomprehensive performance test for coordinated engagement on a variety ofweapons.